Care to LGBTQIA+ people and the non applicability of the principles of the SUS: Universality, Integrality and Equity (Research, Society and Development, 2021)
Objective: To analyze the scientific production of nursing on care for the LGBTQIA+ population in the health service. Materials and methods: This is an integrative literature review article on the scientific production of care for the LGBTQIA+ population in the health service. Covering research: theoretical and methodological literature, which point to the studies carried out previously, making it possible to draw conclusions on the subject of interest. Articles between 2018 and 2021 were included, indexed in the databases of the National Health Library (BVS), regardless of the journal of publication. Results: The Ministry of Health has been concerned and seeking to introduce humanized and qualified access for the LGBTQIA+ population. The evolution has brought positive results and a certain visibility, so it was observed that even with several questions arising about the need for a more specialized look, there was no greater progress than the National LGBT Policy that was written in 2011. Final considerations: It points out as a priority, through this review and all the aspects analyzed regarding the service to the LGBTQIA+ population and the non-applicability of the SUS principles, the need for more studies involving the theme, it is possible to recognize the risks that the LGBTQIA+ population is vulnerable , and how much should be improved the links to the service, to improve the consultation and reach the objective which is to guide and get closer.